Assistance for Pregnant Women with Chronic Energy Deficiency to Improve Nutritional Status - Fibrila, Firda; May Nurisgainti Dewi, Lia; Vebriyanti, Amalia; Azzahra, Nabila Raisha; Nuriy, Afina Rahmania; Sitiafara, Telinta; Ridwan, M. (CV. Media Digital Publikasi Indonesia, 2024)
Chronic energy deficiency (CED) in pregnant women is a major risk factor contributingthe poor nutritional status of mothers and their unborn babies. Promotive efforts are needed to improve maternal health status during pregnancy This community service activity was carried out by a team of students from Tanjung Karang Polytechnic along with Pekon Srikaton officials and Adiluwih Health Center, health workers. The purpose is to conduct educational and mentoring programs in an effort to improve nutritional status of pregnant women suffering from chronic energy deficiency (CED). The implementation of community service activities uses observation, counseling, and family empowerment methods. The targets of activity were 2 pregnant women suffering from CED. Assistance is carried out for 20 days for pregnant women starting from data collection, introspective surveys, health checks and education for pregnant women. This activity gave positive results as evidenced by weight gain of pregnant women and behavioral changes in food consumption. In conclusion, intensive and sustainable assistance has a significant positive impact. Pregnant women experienced an increased understanding of the importance of adequate nutrition during pregnancy, changes in a more balanced diet, and an increase in body weight